Optimal Scheduling of Customer Service Personnel in a Call Centre - Vokshi, Arber (My University, 2023)
This project has studied the ability to schedule staff in customer service at Telia Sverige AB using a well-known optimisation algorithm called ‘column generation’. Two mathematical models have been constructed, one for obtaining the amount of shifts required to satisfy the given demand and to which the column generation algorithm is applied, the other for distributing those shifts among employees. Also, one way of generating shifts is presented in detail, involving repeatedly solving a shortest path problem for a weighted, directed graph. The objective of this project was to see how well a more optimisation-based approach compares to the already in-use system at the company. After obtaining the results it was concluded that an optimisation-based approach works quite well for problems of this nature, but that additional real-world parameters need to be taken into account before the model can be used in a call centre
Keywords: Mathematical optimisation, column generation, scheduling problem, call centre optimisation, shortest path problem